2003
DOI: 10.1002/art.10882
|View full text |Cite
|
Sign up to set email alerts
|

Functional and prognostic relevance of the −173 polymorphism of the macrophage migration inhibitory factor gene in systemic‐onset juvenile idiopathic arthritis

Abstract: Objective. To address the functional and prognostic relevance of the -173 single-nucleotide G-to-C polymorphism of the macrophage migration inhibitory factor (MIF) gene in patients with systemic-onset juvenile idiopathic arthritis (systemic-onset JIA) by evaluating its association with serum and synovial fluid levels of MIF, with glucocorticoid requirement, and with the outcome of the disease.Methods. A total of 136 patients with systemiconset JIA were studied, including 98 patients from the British Paediatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
117
0
5

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 173 publications
(124 citation statements)
references
References 29 publications
2
117
0
5
Order By: Relevance
“…Second, MIF levels were also found to be increased in synovial fluid and synovial tissue from patients with RA and from patients with juvenile idiopathic arthritis; in the latter group, this was independent of disease activity as measured by the C-reactive protein levels (6,15,40). These findings indicate that MIF expression is not specific for RA but may also function as an important regulator of immunity in other autoimmune conditions such as systemic lupus erythematosus, multiple sclerosis, and diabetes.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Second, MIF levels were also found to be increased in synovial fluid and synovial tissue from patients with RA and from patients with juvenile idiopathic arthritis; in the latter group, this was independent of disease activity as measured by the C-reactive protein levels (6,15,40). These findings indicate that MIF expression is not specific for RA but may also function as an important regulator of immunity in other autoimmune conditions such as systemic lupus erythematosus, multiple sclerosis, and diabetes.…”
Section: Discussionmentioning
confidence: 85%
“…In contrast with this finding, Barton and colleagues found that the MIF Ϫ173C allele and the MIF CATT 7 repeat were associated with susceptibility to inflammatory arthritis, but they were unable to find a correlation with disease severity (14). Susceptibility to juvenile idiopathic arthritis was found to be associated with both functional promotor polymorphisms in the MIF gene (6,15). In addition, the circulating MIF level was found to be increased in individuals with juvenile idiopathic arthritis carrying the MIF Ϫ173C functional variant, and the MIF Ϫ173C allele was suggested to be a predictor of poor outcome in this disease (15).…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…3 However, such associations are seen mostly in polyarticular JIA, but not in s-JIA. Other genes including MIF, IL6, IL10 and TNF are reported to be associated with s-JIA in different populations and subtypes, [4][5][6][7][8] although these genes account for only a small part of the total genetic contribution to JIA. Therefore, the genetic background underlying the s-JIA remains mostly undetermined.…”
Section: Introductionmentioning
confidence: 99%